Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery including same
The development of cobalt-coated lithium-nickel-based composite oxides with uneven and flat surfaces addresses structural issues in lithium secondary batteries, enhancing charge/discharge efficiency and lifespan while maintaining high energy density.
Patent Information
- Application Number
- JP2022128906
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-03
- Filing Date
- 2022-08-12
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-08-12
AI Technical Summary
Existing lithium secondary batteries face issues with structural collapse and increased resistance due to repeated charging and discharging, leading to reduced lifespan and capacity, particularly in high-energy density applications.
A positive electrode active material comprising lithium-nickel-based composite oxides with a cobalt coating on secondary or single particles, featuring both uneven and flat surfaces, is developed through a specific heat treatment process to enhance structural stability and surface area.
The cobalt-coated lithium-nickel-based composite oxides exhibit improved charge/discharge efficiency, high capacity, and extended lifespan, maintaining high energy density and safety in lithium secondary batteries.
Smart Images

Figure 0007607619000008 
Figure 0007607619000009 
Figure 0007607619000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material for a lithium secondary battery, a method for producing the same, and a lithium secondary battery including the same. [Background technology]
[0002] Lithium secondary batteries, which have high energy density yet are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, laptops, smartphones, etc. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage sources for hybrid and electric vehicles.
[0003] In order to realize a lithium secondary battery suitable for such applications, various positive electrode active materials have been investigated. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, such positive electrode active materials have problems such as structure collapse or cracks occurring as charging and discharging are repeated, which reduces the long-term life of the lithium secondary battery, and resistance increases, resulting in insufficient capacity characteristics. Therefore, there is a need to develop a new positive electrode active material that can achieve high capacity and high energy density while ensuring long-term life characteristics. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides a positive electrode active material for a lithium secondary battery that realizes high capacity while improving life characteristics and safety, a method for producing the same, and a lithium secondary battery including the same. [Means for solving the problem]
[0005] In one embodiment, there is provided a positive electrode active material for a lithium secondary battery, comprising: a first positive electrode active material comprising a lithium-nickel-based composite oxide and including secondary particles formed by agglomeration of a plurality of primary particles, and a cobalt coating portion located on a surface of the secondary particles; and a second positive electrode active material comprising a lithium-nickel-based composite oxide and including a single particle and a cobalt coating portion located on a surface of the single particle, the second positive electrode active material having an uneven surface with unevenness and a flat surface without unevenness.
[0006] In another embodiment, there is provided a method for producing a positive electrode active material for a lithium secondary battery, comprising: mixing a first nickel-based hydroxide and a lithium raw material, and performing a first heat treatment to prepare a first nickel-based oxide in the form of secondary particles in which a plurality of primary particles are aggregated; mixing a second nickel-based hydroxide and a lithium raw material, and performing a second heat treatment to prepare a second nickel-based oxide in the form of single particles; and mixing the first nickel-based oxide, the second nickel-based oxide, and a cobalt raw material, and performing a third heat treatment.
[0007] In yet another embodiment, there is provided a lithium secondary battery including a positive electrode containing the positive electrode active material, a negative electrode, and an electrolyte. Effect of the Invention
[0008] A positive electrode active material for a lithium secondary battery prepared according to an embodiment and a lithium secondary battery including the same can achieve high capacity and high energy density, and also exhibit excellent charge / discharge efficiency, life characteristics, and safety. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. [Diagram 2] 4 is a scanning electron microscope photograph of a second positive electrode active material of Example 1. [Diagram 3] 11 is a scanning electron microscope photograph of the second positive electrode active material after cobalt coating and before the third heat treatment in Example 2. [Figure 4]1 is a scanning electron microscope photograph of the final second positive electrode active material in Example 2. [Diagram 5] 1 is a scanning electron microscope photograph of a second positive electrode active material of Comparative Example 1. [Figure 6] 1 is a scanning electron microscope photograph of a second positive electrode active material of Comparative Example 2. [Figure 7] 1 is a photograph showing a mapping of cobalt element by a scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) analysis of a second positive electrode active material according to Example 1. [Figure 8] 1 is a photograph showing mapping of cobalt element by SEM-EDS analysis of a second positive electrode active material according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the accompanying drawings, in which: FIG.
[0011] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.
[0012] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.
[0013] It is to be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but do not preclude the possibility of the presence or addition of one or more other features, numbers, steps, components, or combinations thereof.
[0014] In the drawings, the thickness of the various layers and regions is exaggerated for clarity, and similar parts are designated by the same reference numerals throughout the specification. When a part, such as a layer, film, region, plate, etc., is described as being "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is described as being "directly on" another part, it means that there is no other part between them.
[0015] In addition, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.
[0016] The average particle size can be measured by a method well known to those skilled in the art, for example, by using a particle size analyzer or a transmission electron microscope or a scanning electron microscope. Alternatively, the average particle size can be calculated by measuring the number of particles in each particle size range using a dynamic light scattering method and performing data analysis. Unless otherwise defined, the average particle size can refer to the diameter of particles with a cumulative volume of 50% by volume (D50) in the particle size distribution.
[0017] Here, "or" is not to be construed in an exclusive sense; for example, "A or B" is to be construed as including A, B, A+B, etc.
[0018] positive electrode active material In one embodiment, a positive electrode active material for a lithium secondary battery is provided, the positive electrode active material comprising a first positive electrode active material, the first positive electrode active material being in the form of secondary particles formed by agglomeration of a plurality of primary particles, and a cobalt coating portion located on the surface of the secondary particles, and a second positive electrode active material, the second positive electrode active material being in the form of single particles, the second positive electrode active material having a concave-convex surface with concaves and convexes and a flat surface without concaves and convexes. Such a positive electrode active material can exhibit improved life characteristics while realizing high capacity and high energy density.
[0019] First positive electrode active material The first positive electrode active material has a polycrystal form and includes secondary particles formed by agglomeration of at least two primary particles.
[0020] According to an embodiment, the first positive electrode active material includes a cobalt coating portion located on a surface of the secondary particle. The cobalt coating portion may be located on the entire surface of the secondary particle or at least a portion of the surface of the secondary particle. By being coated with cobalt, the first positive electrode active material can effectively prevent structural collapse due to repeated charging and discharging, and can improve room temperature and high temperature life characteristics.
[0021] The cobalt coating portion includes a cobalt-containing compound. The cobalt-containing compound may be, for example, cobalt oxide, cobalt hydroxide, cobalt carbonate, a composite thereof, or a mixture thereof, and may further include lithium and / or nickel. For example, the cobalt-containing compound may be lithium cobalt oxide.
[0022] The content of the cobalt coating portion in the first positive electrode active material may be 0.01 mol% to 7 mol% relative to the entire first positive electrode active material, for example, 0.01 mol% to 6 mol%, 0.1 mol% to 5 mol%, 0.5 mol% to 4 mol%, 1 mol% to 5 mol%, or 2 mol% to 5 mol%, or may be 0.01 atomic% to 7 atomic%, 0.1 atomic% to 5 atomic%, or 0.5 atomic% to 4 atomic%. In this case, a lithium secondary battery including the first positive electrode active material can achieve excellent room temperature and high temperature life characteristics.
[0023] The thickness of the cobalt coating portion in the first positive electrode active material is variable depending on the baking temperature during coating, and depending on the baking temperature, cobalt may penetrate into the active material to be coated and / or doped. Thus, the thickness of the cobalt coating layer may be, for example, 1 nm to 2 μm, 1 nm to 1.5 μm, 1 nm to 1 μm, 1 nm to 900 nm, 1 nm to 700 nm, 1 nm to 500 nm, 1 nm to 300 nm, 5 nm to 100 nm, or 5 nm to 50 nm. In this case, a lithium secondary battery including the first positive electrode active material may exhibit excellent room temperature and high temperature life characteristics.
[0024] The average particle size of the first positive electrode active material, that is, the average particle size of the secondary particles, may be 7 μm to 25 μm. For example, it may be 9 μm to 25 μm, 10 μm to 25 μm, 15 μm to 25 μm, or 10 μm to 20 μm. The average particle size of the secondary particles of the first positive electrode active material is equal to or larger than the average particle size of the second positive electrode active material of single particles described below. The positive electrode active material according to one embodiment may be in a form in which the first positive electrode active material, which is polycrystalline and large particles, is mixed with the second positive electrode active material, which is single particles and small particles, and this can improve the mixture density and realize high capacity and high energy density.
[0025] Here, the average particle diameter means the diameter of a particle having a cumulative volume of 50% by volume in the particle size distribution, that is, D50. The average particle diameter may be measured through an electron microscope photograph such as a scanning electron microscope or a transmission electron microscope. For example, 30 particles in the form of secondary particles are arbitrarily selected from a scanning electron microscope photograph of the positive electrode active material, and their sizes (particle diameter or major axis length) are measured to obtain a particle size distribution, and D50 is calculated and taken as the average particle diameter of the first positive electrode active material.
[0026] The first positive electrode active material is a nickel-based positive electrode active material and includes a lithium nickel-based composite oxide (or a first nickel-based oxide). The content of nickel in the lithium nickel-based composite oxide may be 30 mol% or more based on the total amount of elements excluding lithium and oxygen, for example, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and may be 99.9 mol% or less, or 99 mol% or less. As an example, the content of nickel in the lithium nickel-based composite oxide is higher than the content of each of other metals such as cobalt, manganese, and aluminum. When the content of nickel satisfies the above range, the positive electrode active material can exhibit excellent battery performance while achieving high capacity.
[0027] Specifically, the first positive electrode active material may include a lithium nickel-based composite oxide represented by the following Chemical Formula 1. [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O2
[0028] In the above formula 1, 0.9≦a1≦1.8, 0.3≦x1≦1, and 0≦y1≦0.7; M 1 and M. 2are each independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or combinations thereof. In the above Chemical Formula 1, 0.4≦x1≦1 and 0≦y1≦0.6 may be satisfied, or 0.5≦x1≦1 and 0≦y1≦0.5 may be satisfied, or 0.6≦x1≦1 and 0≦y1≦0.4 may be satisfied, or 0.7≦x1≦1 and 0≦y1≦0.3 may be satisfied, or 0.8≦x1≦1 and 0≦y1≦0.2 may be satisfied, or 0.9≦x1≦1 and 0≦y1≦0.1 may be satisfied.
[0029] The first positive electrode active material may include, for example, a lithium nickel-based composite oxide represented by the following Chemical Formula 2. [Chemical formula 2] Li a2 Ni x2 Co y2 M 3 1-x2-y2 O2
[0030] In the above formula 2, 0.9≦a2≦1.8, 0.3≦x2<1, 0 <y2≦0.7であり、M 3 is Al, B, Ba, Ca, Ce, Cr, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or combinations thereof. In the above Chemical Formula 2, 0.3≦x2≦0.99 and 0.01≦y2≦0.7 may be satisfied, or 0.4≦x2≦0.99 and 0.01≦y2≦0.6 may be satisfied, or 0.5≦x2≦0.99 and 0.01≦y2≦0.5 may be satisfied, or 0.6≦x2≦0.99 and 0.01≦y2≦0.4 may be satisfied, or 0.7≦x2≦0.99 and 0.01≦y2≦0.3 may be satisfied, or 0.8≦x2≦0.99 and 0.01≦y2≦0.2 may be satisfied, or 0.9≦x2≦0.99 and 0.01≦y2≦0.1 may be satisfied.
[0031] The first positive electrode active material may include, for example, a compound represented by the following Chemical Formula 3. [Chemical formula 3] Li a3 Nix3 Co y3 M 4 z3 M 5 1-x3-y3-z3 O2
[0032] In the above formula 3, 0.9≦a3≦1.8, 0.3≦x3≦0.98, 0.01≦y3≦0.69, and 0.01≦z3≦0.69; M 4 is Al, Mn, or a combination thereof, and M 5 is B, Ba, Ca, Ce, Cr, F, Fe, Mg, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or combinations thereof. In the formula 3, 0.4≦x3≦0.98, 0.01≦y3≦0.59, and 0.01≦z3≦0.59 may be satisfied, 0.5≦x3≦0.98, 0.01≦y3≦0.49, and 0.01≦z3≦0.49 may be satisfied, or 0.6≦x3≦0.98, 0.01≦y3≦0.39, and 0.01≦z3≦0.39 may be satisfied. or 0.7≦x3≦0.98, 0.01≦y3≦0.29, and 0.01≦z3≦0.29, or 0.8≦x3≦0.98, 0.01≦y3≦0.19, and 0.01≦z3≦0.19, or 0.9≦x3≦0.98, 0.01≦y3≦0.09, and 0.01≦z3≦0.09.
[0033] On the other hand, the maximum roughness of the surface of the first positive electrode active material may be, for example, 3 nm to 100 nm, 5 nm to 50 nm, 3 nm to 15 nm, or 3 nm to 10 nm, the average roughness may be 0.2 nm to 10 nm, 0.5 nm to 3 nm, 0.2 nm to 1.5 nm, or 0.2 nm to 1 nm, and the root-mean-square roughness may be 0.5 nm to 10 nm, 0.7 nm to 3 nm, 0.5 nm to 2 nm, or 0.5 nm to 1.5 nm. Details of the meanings and measuring methods of the maximum roughness, average roughness, and root-mean-square roughness will be described later in the section on the second positive electrode active material.
[0034] Second positive electrode active material The second positive electrode active material is in the form of a single particle, which means that the particle does not have a grain boundary and exists alone, and may mean a monolith structure or a single body structure or a non-aggregated particle in which the particles are morphologically present in an independent phase without mutual aggregation, for example, a single crystal. The positive electrode active material according to an embodiment includes such a second positive electrode active material, and thus can exhibit improved life characteristics while realizing high capacity and high energy density.
[0035] The shape of the second positive electrode active material is not particularly limited, and may have various shapes such as a polyhedron, a sphere, an ellipse, a plate, a rod, an irregular shape, etc. The single-particle second positive electrode active material according to an embodiment may have a polyhedron structure having two or more faces.
[0036] According to an embodiment, the second positive electrode active material includes a cobalt coating portion located on the surface of a single particle. By being coated with cobalt, the second positive electrode active material can effectively prevent the structure from collapsing due to repeated charging and discharging, and can improve the room temperature and high temperature life characteristics.
[0037] The cobalt coating portion includes a cobalt-containing compound. The cobalt-containing compound may be, for example, cobalt oxide, cobalt hydroxide, cobalt carbonate, a composite thereof, or a mixture thereof, and may further include lithium and / or nickel. For example, the cobalt-containing compound may be lithium cobalt oxide.
[0038] In a method for manufacturing a positive electrode active material according to an embodiment described below, the first positive electrode active material and the second positive electrode active material are not individually coated with cobalt, but the first nickel-based oxide, the second nickel-based oxide, and the cobalt raw material are mixed together and then a third heat treatment is performed to perform simultaneous coating (or simultaneous firing). As a result, it is confirmed that cobalt is effectively coated only on a portion of the crystal surface of the single particle second positive electrode active material, and unevenness occurs in this portion. As a result, one single particle of the second positive electrode active material includes both an uneven surface having a specific shape of unevenness and a flat or smooth flat surface. This is understood to be because cobalt is effectively coated only on the crystal surface where lithium ions are likely to enter and exit, resulting in unevenness. Such a second positive electrode active material has increased surface roughness on a specific surface, and the specific surface area of the second positive electrode active material and the entire positive electrode active material including the same is increased. A lithium secondary battery including such a positive electrode active material has improved initial discharge capacity, charge / discharge efficiency, and life characteristics.
[0039] The unevenness of the uneven surface may be linear or amorphous. The uneven surface may be expressed as a form in which the cobalt-containing compound is attached in a linear or amorphous form, or a form in which the cobalt-containing compound covers the surface of a single particle in a bumpy form. This form is different from the existing island-shaped coating.
[0040] A single particle of the second positive electrode active material may include an uneven surface having a high surface roughness and a flat surface having a low surface roughness. That is, the uneven surface of the second positive electrode active material has a high surface roughness. The surface roughness may be measured by a surface roughness measuring device, for example, an optical profiler, using a photograph of an object taken by an atomic force microscopy (AFM) or the like.
[0041] The maximum surface roughness (R maxThe term "peak to peak height" or "maximum roughness depth" can refer to the vertical distance between the highest peak and the lowest valley within the reference length of the roughness profile. a Average roughness (R ) is also called center line average roughness and can mean the arithmetic mean of the absolute value of the ordinate (length from the center line to the peak) within the reference length of the roughness profile. q Root mean square roughness (rms) can mean the root mean square (rms) of the longitudinal values within the sampling length of the roughness profile. For such surface roughness, reference can be made to the parameter definitions and measurement methods defined in KS B 0601 or ISO 4287 / 1.
[0042] The uneven surface of the second positive electrode active material has a maximum roughness (R max ; peak to peak height) may be 18 nm or more, for example, 20 nm or more, and may be 18 nm to 100 nm, 18 nm to 80 nm, 19 nm to 60 nm, or 20 nm to 40 nm. In this case, the positive electrode active material for a lithium secondary battery containing the second positive electrode active material exhibits high energy density and high capacity, and can achieve excellent charge / discharge efficiency and life characteristics.
[0043] The uneven surface of the second positive electrode active material has an average roughness (R a ; average roughness) may be 1.9 nm or more, for example, 2.0 nm or more, or may be 1.9 nm to 10 nm, 1.9 nm to 8.0 nm, 1.9 nm to 6.0 nm, 1.9 nm to 5.0 nm, or 2.0 nm to 10 nm. In this case, the positive electrode active material for lithium secondary batteries containing the second positive electrode active material exhibits high energy density and high capacity, and can achieve excellent charge / discharge efficiency and life characteristics.
[0044] The uneven surface of the second positive electrode active material has a root mean square roughness (R q ; root mean square roughness) may be 2.3 nm or more, for example, 2.4 nm or more, or may be 2.3 nm to 10 nm, 2.3 nm to 8 nm, 2.3 nm to 6 nm, 2.3 nm to 5 nm, or 2.4 nm to 10 nm. In this case, the positive electrode active material for a lithium secondary battery containing the second positive electrode active material exhibits high energy density and high capacity, and can realize excellent charge / discharge efficiency and life characteristics.
[0045] In contrast, the flat surface of the second positive electrode active material may exhibit a lower surface roughness than the uneven surface. For example, the flat surface of the second positive electrode active material may exhibit a maximum roughness (R max ) may be 15 nm or less, for example, 0.1 nm to 14 nm, or 1 nm to 13 nm. In addition, the flat surface of the second positive electrode active material may have an average roughness (R a The flat surface of the second positive electrode active material may have a root mean square roughness (R q ) may be 2.2 nm or less, for example, 0.1 nm to 2.2 nm, or 0.5 nm to 2.1 nm.
[0046] The second positive electrode active material, which has both uneven and flat surfaces in this manner, can achieve high capacity and high energy density while having a stable structure that does not collapse during charging and discharging of the battery, and can exhibit excellent life characteristics.
[0047] The content of the cobalt coating portion in the second positive electrode active material may be 0.01 mol% to 10 mol% relative to the entire second positive electrode active material, for example, 0.05 mol% to 9 mol%, 0.1 mol% to 8 mol%, 0.5 mol% to 7 mol%, or 1 mol% to 6 mol%, or may be 0.01 atomic% to 10 atomic%, 0.1 atomic% to 8 atomic%, or 0.5 atomic% to 6 atomic%. In this case, a lithium secondary battery including the second positive electrode active material can achieve excellent room temperature and high temperature life characteristics.
[0048] The ratio of the uneven surface to the total surface area of the second positive electrode active material may be about 40% to 80%, for example, 45% to 80%, or 50% to 75%. The ratio of the flat surface to the total surface area of the second positive electrode active material may be about 20% to 60%, for example, 20% to 55%, or 25% to 50%. By including the uneven surface and the flat surface at such a ratio, the second positive electrode active material can achieve high capacity while simultaneously exhibiting long life characteristics.
[0049] The thickness of the cobalt coating portion in the second positive electrode active material may be about 1 nm to 2 μm, for example, 1 nm to 1 μm, 1 nm to 900 nm, 1 nm to 700 nm, 1 nm to 500 nm, 1 nm to 300 nm, 5 nm to 100 nm, or 5 nm to 50 nm. In this case, a lithium secondary battery including the second positive electrode active material may exhibit excellent room temperature and high temperature life characteristics. The thickness of the cobalt coating portion may be measured through an electron microscope photograph of the positive electrode active material.
[0050] On the other hand, the second positive electrode active material can have faces with different cobalt contents. That is, the second positive electrode active material can have both a face with a high cobalt content and a face with a low cobalt content in one single particle. For example, the cobalt content in the face with a high cobalt content may be 30 at% to 70 at%, or 35 at% to 65 at%, based on the total transition metals excluding lithium. The cobalt content in the face with a low cobalt content may be 1 at% to 30 at%, or 3 at% to 25 at%, based on the total transition metals excluding lithium. In addition, the ratio of the face with a high cobalt content in one single particle may be 20% to 50%, and the ratio of the face with a low cobalt content may be 50% to 80%. Such a second positive electrode active material can improve the capacity and life characteristics of a battery.
[0051] The average particle size of the second positive electrode active material, that is, the average particle size of the single particle, may be 0.05 μm to 10 μm, for example, 0.1 μm to 8 μm, 0.1 μm to 7 μm, 0.1 μm to 6 μm, 0.1 μm to 10 μm, or specifically, 1 μm to 5 μm. The particle size of the second positive electrode active material is equal to or smaller than that of the first positive electrode active material, and the density of the positive electrode active material can be further increased. Here, the average particle size means the diameter of the particle whose cumulative volume is 50 volume % in the particle size distribution, that is, D50. As an example, 30 particles in the form of single particles are arbitrarily selected from a scanning electron microscope photograph of the positive electrode active material, and the size (particle size or length of the major axis) of these particles is measured to obtain a particle size distribution, and D50 is calculated and taken as the average particle size of the second positive electrode active material.
[0052] The BET specific surface area of the entire positive electrode active material including the first positive electrode active material and the second positive electrode active material is 0.2 m 2 / g~0.6m 2 / g, for example, 0.3m 2 / g~approx.0.5m 2 / g, 0.3m 2 / g~approx.0.4m 2 / g. In this case, the positive electrode active material can achieve excellent charge / discharge efficiency and life characteristics.
[0053] The BET specific surface area may be measured by a nitrogen gas adsorption method using, for example, a specific surface area measuring device ASAP 2020 manufactured by Micromeritics. Specifically, about 0.4 g of a positive electrode active material sample is filled into a cell, pretreated by heating at 220°C, cooled to the temperature of liquid nitrogen, and saturated adsorbed with a gas of 30% nitrogen and 70% He, and then heated to room temperature to measure the amount of desorbed gas. The specific surface area can be calculated from the obtained results by a normal BET method.
[0054] The second positive electrode active material includes a lithium nickel-based composite oxide (or a second nickel-based oxide) as a nickel-based active material. The content of nickel in the lithium nickel-based composite oxide may be 30 mol% or more based on the total amount of elements excluding lithium and oxygen, for example, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and may be 99.9 mol% or less, or 99 mol% or less. As an example, the content of nickel in the lithium nickel-based composite oxide is higher than the content of each of other metals such as cobalt, manganese, and aluminum. When the content of nickel satisfies the above range, the positive electrode active material can exhibit excellent battery performance while achieving high capacity.
[0055] The second positive electrode active material may include, for example, a lithium nickel-based composite oxide represented by the following Chemical Formula 11. [Chemical formula 11] Li a11 Ni x11 M 11 y11 M 12 1-x11-y11 O2
[0056] In the above formula 11, 0.9≦a11≦1.8, 0.3≦x11≦1, and 0≦y11≦0.7; M 11 and M. 12 are each independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or combinations thereof. In the above Chemical Formula 11, 0.4≦x11≦1 and 0≦y11≦0.6 may be satisfied, or 0.5≦x11≦1 and 0≦y11≦0.5 may be satisfied, or 0.6≦x11≦1 and 0≦y11≦0.4 may be satisfied, or 0.7≦x11≦1 and 0≦y11≦0.3 may be satisfied, or 0.8≦x11≦1 and 0≦y11≦0.2 may be satisfied, or 0.9≦x11≦1 and 0≦y11≦0.1 may be satisfied.
[0057] The second positive electrode active material may include, for example, a lithium nickel-based composite oxide represented by the following Chemical Formula 12. [Chemical formula 12] Li a12 Ni x12 Co y12 M 13 1-x12-y12 O2
[0058] In the above formula 12, 0.9≦a12≦1.8, 0.3≦x12<1, 0 <y12≦0.7であり、M 13 is Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or combinations thereof. In the above Chemical Formula 12, 0.3≦x12≦0.99 and 0.01≦y12≦0.7 may be satisfied, 0.4≦x12≦0.99 and 0.01≦y12≦0.6 may be satisfied, 0.5≦x12≦0.99 and 0.01≦y12≦0.5 may be satisfied, 0.6≦x12≦0.99 and 0.01≦y12≦0.4 may be satisfied, 0.7≦x12≦0.99 and 0.01≦y12≦0.3 may be satisfied, 0.8≦x12≦0.99 and 0.01≦y12≦0.2 may be satisfied, or 0.9≦x12≦0.99 and 0.01≦y12≦0.1 may be satisfied.
[0059] The second positive electrode active material may include, for example, a lithium nickel cobalt composite oxide represented by the following Chemical Formula 13: [Chemical formula 13] Li a13 Ni x13 Co y13 M 14 z13 M 15 1-x13-y13-z13 O2
[0060] In the formula 13, 0.9≦a13≦1.8, 0.3≦x13≦0.98, 0.01≦y13≦0.69, and 0.01≦z13≦0.69; M 14 is Al, Mn, or a combination thereof, and M 15is B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or combinations thereof. In the formula 13, 0.4≦x13≦0.98, 0.01≦y13≦0.59, and 0.01≦z13≦0.59 may be satisfied, 0.5≦x13≦0.98, 0.01≦y13≦0.49, and 0.01≦z13≦0.49 may be satisfied, or 0.6≦x13≦0.98, 0.01≦y13≦0.39, and 0.01≦z13≦0.39 may be satisfied. or 0.7≦x13≦0.98, 0.01≦y13≦0.29, and 0.01≦z13≦0.29, or 0.8≦x13≦0.98, 0.01≦y13≦0.19, and 0.01≦z13≦0.19, or 0.9≦x13≦0.98, 0.01≦y13≦0.09, and 0.01≦z13≦0.09.
[0061] In one embodiment of the positive electrode active material, the first positive electrode active material is contained in an amount of 50% by weight to 90% by weight, and the second positive electrode active material is contained in an amount of 10% by weight to 50% by weight, based on the total amount of the first positive electrode active material and the second positive electrode active material. The first positive electrode active material is contained in an amount of, for example, 60% by weight to 90% by weight, or 70% by weight to 90% by weight, and the second positive electrode active material is contained in an amount of 10% by weight to 40% by weight, or 10% by weight to 30% by weight. When the content ratio of the first positive electrode active material to the second positive electrode active material is as described above, the positive electrode active material containing them can realize a high capacity, improve the mixture density, and exhibit a high energy density.
[0062] Method for producing positive electrode active material In one embodiment, there is provided a method for producing a positive electrode active material for a lithium secondary battery, comprising mixing a first nickel-based hydroxide and a lithium source and performing a first heat treatment to prepare a first nickel-based oxide, mixing a second nickel-based hydroxide and a lithium source and performing a second heat treatment to prepare a second nickel-based oxide, and mixing the first nickel-based oxide, the second nickel-based oxide, and a cobalt source and performing a third heat treatment to obtain a final positive electrode active material including the first positive electrode active material and the second positive electrode active material.
[0063] Here, the first nickel-based oxide and the first positive electrode active material are in the form of secondary particles formed by agglomeration of a plurality of primary particles, and the second nickel-based oxide and the second positive electrode active material are in the form of single particles. The first positive electrode active material is a material in which the surface of the first nickel-based oxide is coated with cobalt, and the second positive electrode active material is a material in which the surface of the second nickel-based oxide is coated with cobalt.
[0064] In one embodiment, the first and second positive electrode active materials are not individually cobalt-coated, but the first and second nickel-based oxides are mixed and cobalt-coated simultaneously. In this way, the single-particle second positive electrode active material coated with cobalt has both a bumpy surface and a smooth surface, and thus has high surface roughness and specific surface area. A positive electrode active material for a lithium secondary battery including such a second positive electrode active material exhibits a high specific surface area and can achieve excellent capacity and life characteristics.
[0065] The first nickel-based hydroxide and the second nickel-based hydroxide are precursors of a positive electrode active material, and may each independently be a nickel hydroxide, a nickel-based composite hydroxide containing elements other than nickel, a nickel-metal composite hydroxide containing metals other than nickel, or a nickel-transition metal composite hydroxide containing transition metals other than nickel.
[0066] For example, the first nickel hydroxide and the second nickel hydroxide may each independently be represented by the following chemical formula 21. [Chemical formula 21] Ni x21 M 21 y21 M 22 1-x21-y21 (OH)2
[0067] In the above formula 21, 0.3≦x21≦1, 0≦y21≦0.7, M 21 and M. 22are each independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or combinations thereof.
[0068] The particle size of the first nickel hydroxide may be 10 μm to 30 μm, for example, 10 μm to 25 μm, 15 μm to 25 μm, or 10 μm to 20 μm. The particle size of the second nickel-based hydroxide may be 1 μm to 9 μm, for example, 2 μm to 9 μm, 2 μm to 8 μm, or 3 μm to 7 μm. Here, the particle size of the first nickel-based hydroxide is analyzed by a particle size analyzer using a laser diffraction method, and may mean, for example, D50.
[0069] The lithium source may be, for example, Li2CO3, LiOH, hydrates thereof, or a combination thereof as a lithium source for the positive electrode active material.
[0070] When the first nickel-based hydroxide and the lithium raw material are mixed, the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the first nickel-based hydroxide may be, for example, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1.0 or more, and may be 1.8 or less, 1.5 or less, 1.2 or less, 1.1 or less, or 1.05 or less.
[0071] The first heat treatment may be performed in an oxidizing gas atmosphere, for example, an oxygen atmosphere or an air atmosphere. The first heat treatment may be performed at, for example, 600°C to 900°C or 600°C to 800°C, for example, 5 to 20 hours or 5 to 15 hours. The first nickel-based oxide obtained by the first heat treatment may also be called a first lithium-nickel-based oxide.
[0072] When the second nickel-based hydroxide and the lithium raw material are mixed, the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the second nickel-based hydroxide may be, for example, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1.0 or more, and may be 1.8 or less, 1.5 or less, 1.2 or less, 1.1 or less, or 1.05 or less.
[0073] The second heat treatment is also performed in an oxidizing gas atmosphere, and may be performed, for example, in an oxygen atmosphere or an air atmosphere. The second heat treatment may be performed, for example, at 800°C to 1100°C or 900°C to 1000°C, and may be performed, for example, for 5 to 20 hours or 5 to 15 hours. The second nickel-based oxide obtained by the second heat treatment may be expressed as a second lithium-nickel-based oxide.
[0074] The second nickel-based oxide has a single particle form, and the single particle form can be obtained by adjusting the conditions of the second heat treatment, such as the temperature and time, and the single particle form can also be obtained by adjusting various conditions when synthesizing the second nickel-based hydroxide by a co-precipitation method.
[0075] The method for producing a positive electrode active material for a lithium secondary battery may further include mixing the second nickel-based hydroxide and the lithium raw material, performing a second heat treatment, and then pulverizing the resulting material, thereby obtaining a single particle of the second nickel-based oxide. The pulverization is performed using various pulverizing devices such as a jet mill. Here, the pulverization of the resulting material is a process of obtaining a single particle of active material, and is different from general crushing of active material.
[0076] In the process of mixing the first nickel-based oxide and the second nickel-based oxide, the weight ratio of the first nickel-based oxide to the second nickel-based oxide may be 9:1 to 5:5, for example, 9:1 to 6:4, or 8:2 to 7:3. When the mixing ratio of the first nickel-based oxide to the second nickel-based oxide satisfies the above-mentioned range, the produced positive electrode active material can exhibit high capacity and high energy density, and can exhibit high plate density.
[0077] Next, the first nickel-based oxide, the second nickel-based oxide, and the cobalt raw material are mixed and subjected to a third heat treatment to proceed with cobalt coating. The cobalt coating may be performed in a dry or wet manner. For example, the first nickel-based oxide, the second nickel-based oxide, and the cobalt raw material are mixed without a solvent, and then the third heat treatment is performed to proceed with dry coating. Here, a lithium-containing compound such as lithium hydroxide can be added together with the cobalt compound. At this time, the amount of the lithium-containing compound added may be 0.01 to 5 molar parts, or 0.1 to 3 molar parts, based on 100 molar parts of the total metal content of the positive electrode active material. The lithium raw material may be mixed in an amount of 1 to 4 molar parts with respect to 1 molar part of the cobalt raw material added together, for example, 1.5 to 3 molar parts. That is, the lithium raw material may be added in an amount of 1 to 4 times, or 1.5 to 3 times, the amount of the cobalt raw material.
[0078] Alternatively, the first nickel-based oxide and the second nickel-based oxide may be added to a solvent such as distilled water, mixed and washed, and the cobalt raw material may be dropped to proceed with wet coating, followed by the third heat treatment. At this time, a lithium-containing compound such as lithium hydroxide and / or a pH adjuster such as sodium hydroxide may be added together with the cobalt raw material. The content of the lithium-containing compound is as described above. The pH adjuster may be added in an amount of 0.5 to 5 molar parts per 1 molar part of the cobalt raw material. In this way, the cobalt coating portion according to one embodiment can be effectively formed by using the lithium-containing compound and the pH adjuster.
[0079] The cobalt source may be, for example, a cobalt sulfate, a cobalt oxide, a cobalt nitrate, or the like.
[0080] The cobalt raw material may be mixed such that the amount of cobalt contained in the cobalt raw material is 0.01 to 7 molar parts, or 0.01 to 5 molar parts, or 0.1 to 4 molar parts, when the content of metals excluding lithium in the entire positive electrode active material is 100 molar parts.
[0081] The third heat treatment is carried out in an oxidizing gas atmosphere such as an oxygen or air atmosphere, and may be carried out at, for example, 650° C. to 900° C. or 650° C. to 800° C. The third heat treatment time varies depending on the heat treatment temperature, and is, for example, 5 to 30 hours or 10 to 24 hours.
[0082] Thereafter, the heat treatment is terminated and the mixture is cooled to room temperature to manufacture the cathode active material for a lithium secondary battery according to the embodiment described above. The manufactured cathode active material is a mixture of a first cathode active material including secondary particles formed by agglomeration of primary particles and a second cathode active material in the form of single particles, each of which is coated with cobalt, and the second cathode active material includes both an uneven surface and a flat surface.
[0083] positive electrode The positive electrode for a lithium secondary battery may include a current collector and a positive electrode active material layer located on the current collector. The positive electrode active material layer includes a positive electrode active material, and may further include a binder and / or a conductive material.
[0084] The binder serves to effectively adhere the positive electrode active material particles to each other and to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, and the like.
[0085] The content of the binder in the positive electrode active material layer may be about 1% by weight to about 5% by weight based on the total weight of the positive electrode active material layer.
[0086] The conductive material is used to impart conductivity to the electrodes, and any material that is electronically conductive without causing a chemical change in the battery that is constructed can be used. Examples of the conductive material that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, and carbon nanotubes; metal-based materials containing copper, nickel, aluminum, silver, or the like in the form of metal powder or metal fibers; conductive polymers such as polyphenylene derivatives; and conductive materials containing mixtures of these.
[0087] The content of the conductive material in the positive electrode active material layer may be 1 wt % to 5 wt % based on the total weight of the positive electrode active material layer.
[0088] The positive electrode current collector may be, but is not limited to, an aluminum foil.
[0089] negative electrode The negative electrode for a lithium secondary battery includes a current collector and a negative electrode active material layer located on the current collector. The negative electrode active material layer includes a negative electrode active material, and may further include a binder and / or a conductive material.
[0090] The negative electrode active material includes a material capable of reversibly inserting / extracting lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, or a transition metal oxide.
[0091] The material capable of reversibly inserting / extracting lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof, as a carbon-based negative electrode active material. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, and calcined coke.
[0092] The lithium metal alloy may be an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0093] The material capable of doping and dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. Examples of the Si-based negative electrode active material include silicon, silicon-carbon composite, and SiO x(0 < x < 2), Si-Q alloy (wherein Q is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, and is not Si), examples of the Sn-based negative electrode active material include Sn, SnO2, Sn-R alloy (wherein R is an element selected from the group consisting of an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof, and is not Sn), etc., and at least one of these may be mixed with SiO2 and used. As the elements Q and R, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof can be used.
[0094] The silicon-carbon composite may be, for example, a silicon-carbon composite including a core containing crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon precursor may be coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based heavy oil, or polymer resin such as phenol resin, furan resin, or polyimide resin. At this time, the content of silicon may be 10% by weight to 50% by weight based on the total weight of the silicon-carbon composite. The content of the crystalline carbon may be 10% by weight to 70% by weight based on the total weight of the silicon-carbon composite, and the content of the amorphous carbon may be 20% by weight to 40% by weight based on the total weight of the silicon-carbon composite. Furthermore, the thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle size (D50) of the silicon particles may be 10 nm to 20 μm. The silicon particles may have an average particle size (D50) of preferably 10 nm to 200 nm. The silicon particles may be present in an oxidized form, and in this case, the atomic content ratio of Si:O in the silicon particles, which indicates the degree of oxidation, may be 99:1 to 33:67. The silicon particles may be SiO x In this case, SiO x In the formula, x may range from more than 0 to less than 2.
[0095] The Si-based or Sn-based negative electrode active material may be mixed with a carbon-based negative electrode active material. When the Si-based or Sn-based negative electrode active material is mixed with the carbon-based negative electrode active material, the mixing ratio may be 1:99 to 90:10 by weight.
[0096] The content of the negative electrode active material in the negative electrode active material layer may be 95% by weight to 99% by weight based on the total weight of the negative electrode active material layer.
[0097] In one embodiment, the negative electrode active material layer may further include a binder, and may optionally further include a conductive material. The content of the binder in the negative electrode active material layer may be 1 wt% to 5 wt% based on the total weight of the negative electrode active material layer. When the negative electrode active material layer further includes a conductive material, the negative electrode active material layer may include 90 wt% to 98 wt% of the negative electrode active material, 1 wt% to 5 wt% of the binder, and 1 wt% to 5 wt% of the conductive material.
[0098] The binder serves to adhere the negative active material particles to each other and to the current collector. The binder may be a water-insoluble binder, a water-soluble binder, or a combination thereof.
[0099] Examples of the non-water-soluble binder include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, ethylene propylene copolymers, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or combinations thereof.
[0100] The water-soluble binder may be a rubber-based binder or a polymeric resin binder. The rubber-based binder may be selected from styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and combinations thereof. The polymeric resin binder may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0101] When a water-soluble binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used. The content of such a thickener may be 0.1 to 3 parts by weight per 100 parts by weight of the negative electrode active material.
[0102] The conductive material is used to impart conductivity to the electrode, and any material that is electronically conductive without causing a chemical change in the battery that is constructed can be used. Examples of the conductive material that can be used include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and conductive materials including mixtures thereof.
[0103] The negative electrode current collector may be selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.
[0104] Lithium secondary battery Another embodiment provides a lithium secondary battery including a positive electrode, a negative electrode, a separator located between the positive electrode and the negative electrode, and an electrolyte.
[0105] 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. Referring to FIG 1, a lithium secondary battery 100 according to an embodiment includes a battery cell including a positive electrode 114, a negative electrode 112 facing the positive electrode 114, a separator 113 disposed between the positive electrode 114 and the negative electrode 112, and a lithium secondary battery electrolyte impregnated in the positive electrode 114, the negative electrode 112, and the separator 113, a battery container 120 including the battery cell, and a sealing member 140 sealing the battery container 120. The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0106] The non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move. As the non-aqueous organic solvent, carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvents can be used. As the carbonate-based solvent, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used. The ester solvent may be methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, etc. The ether solvent may be dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc., and the ketone solvent may be cyclohexanone, etc. In addition, examples of the alcohol solvent that can be used include ethyl alcohol and isopropyl alcohol, and examples of the aprotic solvent that can be used include nitriles such as R-CN (wherein R is a C2 to C20 linear, branched, or cyclic hydrocarbon group that can contain a double bond, an aromatic ring, or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes.
[0107] The non-aqueous organic solvents may be used alone or in combination of one or more thereof. When one or more thereof are used in combination, the mixing ratio can be appropriately adjusted according to the desired battery performance, which is widely understood by those skilled in the art.
[0108] In addition, in the case of the carbonate-based solvent, a cyclic carbonate and a chain carbonate can be mixed and used. In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte is excellent.
[0109] The non-aqueous organic solvent may further include an aromatic hydrocarbon-based organic solvent in addition to the carbonate-based solvent, and the carbonate-based solvent and the aromatic hydrocarbon-based organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.
[0110] The aromatic hydrocarbon solvent may be an aromatic hydrocarbon compound represented by the following formula I:
[0111] [ka]
[0112] In the above formula I, R 4 ~R 9 are the same or different and are selected from the group consisting of hydrogen, halogen, an alkyl group having 1 to 10 carbon atoms, a haloalkyl group having 1 to 10 carbon atoms, and combinations thereof.
[0113] Specific examples of the aromatic hydrocarbon solvent include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, and fluorobenzene. and combinations thereof.
[0114] The electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound of the following formula II as a life-promoting additive to improve the battery life.
[0115] [ka]
[0116] In the above formula II, R 10 and R 11 are the same or different and are selected from the group consisting of hydrogen, a halogen group, a cyano group, a nitro group, and a fluorinated alkyl group having 1 to 5 carbon atoms, 10 and R 11is selected from the group consisting of a halogen group, a cyano group, a nitro group, and a fluorinated alkyl group having 1 to 5 carbon atoms, with the proviso that R 10 and R 11 Neither is hydrogen.
[0117] Representative examples of the ethylene carbonate compound include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, fluoroethylene carbonate, etc. When such a life-improving additive is further used, the amount of the additive used can be appropriately adjusted.
[0118] The lithium salt is a material that dissolves in a non-aqueous organic solvent and acts as a source of lithium ions in a battery to enable basic operation of a lithium secondary battery, and plays a role in promoting the movement of lithium ions between a positive electrode and a negative electrode.
[0119] Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide: LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiN(C x F 2x+1 SO2)(C y F 2y+1and lithium difluoro(bisoxalato)borate (LiDFOB).
[0120] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. When the lithium salt concentration is within this range, the electrolyte has appropriate conductivity and viscosity, and therefore can exhibit excellent electrolyte performance and can effectively migrate lithium ions.
[0121] The separator 113 separates the positive electrode 114 and the negative electrode 112 and provides a path for lithium ions to move, and any separator that is commonly used in lithium ion batteries can be used. In other words, any separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability can be used. The separator 113 can include, for example, glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene, or a combination thereof, and can be in the form of a non-woven or woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are mainly used in lithium ion batteries, and coated separators containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multi-layer structure.
[0122] Lithium secondary batteries are classified into lithium ion batteries, lithium ion polymer batteries, and lithium polymer batteries according to the type of separator and electrolyte used, and may be classified into cylindrical, square, coin, pouch, etc. according to the shape, and into bulk type and thin film type according to the size. The structure and manufacturing method of these batteries are widely known in this field, so a detailed description will be omitted.
[0123] The lithium secondary battery according to an embodiment has a high capacity, and is excellent in storage stability at high temperatures, life characteristics, and high rate characteristics, and can be used in electric vehicles (EVs), hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs), and may be used in portable electronic devices, etc.
[0124] Examples of the present invention and comparative examples are described below. The following examples are merely examples of the present invention, and the present invention is not limited to the following examples.
[0125] Example 1 1. Preparation of the first nickel-based oxide in the form of secondary particles First nickel hydroxide (Ni 0.95 Co 0.04 Mn 0.01 (OH)2) and LiOH so that the molar ratio of lithium to the total amount of the transition metals is 1.04, and the mixture is subjected to a first heat treatment at about 750°C for 15 hours in an oxygen atmosphere to obtain a first nickel-based oxide (LiNi 0.95 Co 0.04 Mn 0.01 The first nickel-based oxide thus obtained has an average particle size of about 13.8 μm and is in the form of secondary particles formed by agglomeration of primary particles.
[0126] 2. Preparation of second nickel-based oxide in single particle form [Co-precipitation process] A mixed solution is prepared by dissolving nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O), and manganese sulfate (MnSO4·H2O) in distilled water as a solvent. To form a complex compound, a diluted ammonia water (NH4OH) solution and sodium hydroxide (NaOH) as a precipitant are prepared. The metal raw material mixed solution, ammonia water, and sodium hydroxide are then each placed into the reactor. The reaction is then allowed to proceed for approximately 20 hours while stirring. The slurry solution in the reactor is then filtered and washed with high-purity distilled water, and then dried for 24 hours to obtain a second nickel hydroxide (Ni 0.94 Co 0.05 Mn 0.01 The resulting nickel hydroxide powder has an average particle size of about 4.0 μm and a specific surface area measured by the BET measurement method of about 15 m 2 / g.
[0127] [Oxidation process] The obtained second nickel-based hydroxide and LiOH are mixed so as to satisfy Li / (Ni+Co+Mn)=1.05, and then the mixture is put into a sintering furnace and subjected to a second heat treatment at 910°C for 8 hours in an oxygen atmosphere. The product is then crushed for about 30 minutes to separate / disperse into a large number of second nickel-based oxides having a single particle structure. The obtained second nickel-based oxide (LiNi 0.94 Co 0.05 Mn 0.01 The average particle size of O2) is about 3.7 μm.
[0128] 3. Cobalt coating and final cathode active material fabrication The first nickel-based oxide and the second nickel-based oxide are mixed in a weight ratio of 7:3, and the mixture and water are washed with a stirrer at a weight ratio of 1:1, and then dried at 150°C. 5 moles of lithium hydroxide and 2.5 moles of cobalt oxide are added to 100 moles of the transition metal of the nickel-based oxide, and the mixture is placed in a sintering furnace and subjected to a third heat treatment at about 710°C for 15 hours in an oxygen atmosphere. The sintering furnace is then cooled to room temperature to obtain a final positive electrode active material in which the first and second positive electrode active materials are mixed.
[0129] The final positive electrode active material is a mixture of a first positive electrode active material in the form of secondary particles and a second positive electrode active material in the form of single particles, each of which is coated with cobalt.
[0130] Fig. 2 is a scanning electron microscope image of particles corresponding to the second positive active material in the final positive active material prepared in Example 1. Referring to Fig. 2, it can be seen that the second positive active material, which is a single particle, has an uneven surface and a flat surface formed on the surface.
[0131] 4. Fabrication of the Positive Electrode 95% by weight of the final positive electrode active material, 3% by weight of polyvinylidene fluoride binder, and 2% by weight of carbon nanotube conductive material are mixed in N-methylpyrrolidone solvent to prepare a positive electrode active material slurry. The positive electrode active material slurry is applied to an aluminum current collector, dried, and then rolled to prepare a positive electrode.
[0132] 5. Manufacturing of lithium secondary batteries A coin half cell is manufactured by using the prepared positive electrode and lithium metal counter electrode, placing a polyethylene polypropylene multilayer separator between them, and injecting an electrolyte solution of 1.0 M LiPF6 lithium salt into a solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 50:50.
[0133] Example 2 In "3. Preparation of cobalt coating and final positive active material" of Example 1, a positive active material, a positive electrode, and a battery are manufactured in the same manner as in Example 1, except that the cobalt coating is performed in a wet manner. The cobalt coating process is as follows. The first nickel-based oxide and the second nickel-based oxide are mixed in a weight ratio of 7:3, and then added to distilled water and washed while being mixed. Cobalt sulfate (CoSO4) corresponding to 2.5 mole parts per 100 mole parts of the transition metal of the nickel-based oxide is slowly added to the mixture to perform cobalt coating. Sodium hydroxide (NaOH) is also slowly added. The resulting material is then dried at 150°C for 12 hours. FIG. 3 is a scanning electron microscope image of the second nickel-based oxide corresponding to a single particle in the dried material, and it can be seen that uneven and flat surfaces are formed on the surface.
[0134] The dried material is then placed in a sintering furnace and subjected to a third heat treatment at about 710° C. for 15 hours in an oxygen atmosphere. The sintering furnace is then cooled to room temperature to obtain a final positive electrode active material in which the first and second positive electrode active materials are mixed.
[0135] Figure 4 is a scanning electron microscope image of the particles corresponding to the single particle second positive electrode active material in the final positive electrode active material obtained. Referring to Figure 4, it can be seen that the surface of the second positive electrode active material has an uneven surface and a flat surface. The average particle size of the second positive electrode active material is about 4 μm.
[0136] Comparative Example 1 In "3. Preparation of cobalt coating and final positive electrode active material" of Example 1, the first nickel-based oxide and the second nickel-based oxide are mixed together, and then the cobalt coating is not carried out. Instead, the first nickel-based oxide and the second nickel-based oxide are individually cobalt-coated, and then the mixed materials are mixed. In this embodiment, a positive electrode active material and a battery are prepared in the same manner as in Example 1.
[0137] The cobalt coating process is as follows. The first nickel-based oxide is mixed with 5 molar parts of lithium hydroxide and 3 molar parts of cobalt oxide per 100 molar parts of transition metal, and then the mixture is put into a sintering furnace, and then the mixture is subjected to a third heat treatment at about 700°C for 15 hours in an oxygen atmosphere, and the sintering furnace is cooled to room temperature to obtain a first positive electrode active material. The second nickel-based oxide is mixed with 5 molar parts of lithium hydroxide and 3 molar parts of cobalt oxide per 100 molar parts of transition metal, and then the mixture is put into a sintering furnace, and then the mixture is subjected to a third heat treatment at about 850°C for 15 hours in an oxygen atmosphere, and the sintering furnace is cooled to room temperature to obtain a second positive electrode active material. The first positive electrode active material coated with cobalt and the second positive electrode active material coated with cobalt are mixed in a weight ratio of 7:3 to prepare a final positive electrode active material according to Comparative Example 1.
[0138] Fig. 5 is a scanning electron microscope image of the second positive electrode active material prepared according to Comparative Example 1. Referring to Fig. 5, it can be seen that the surface of the second positive electrode active material prepared according to Comparative Example 1 is smooth and flat without any irregularities.
[0139] Comparative Example 2 A positive electrode active material and a battery were manufactured in the same manner as in Comparative Example 1, except that the third heat treatment step for the second nickel-based oxide was carried out in an oxygen atmosphere at about 700° C. for 15 hours.
[0140] Fig. 6 is a scanning electron microscope image of the second positive electrode active material prepared according to Comparative Example 2. Referring to Fig. 6, it can be seen that the surface of the second positive electrode active material prepared according to Comparative Example 2 is smooth and flat without any irregularities.
[0141] Evaluation example 1: Evaluation of surface roughness of second positive electrode active material The surface roughness of the second positive electrode active material is measured using a surface roughness tester (DME UHV AFM; scan speed 0.25 μm / s, non-contact mode range 250 nm × 250 nm) using an atomic force microscope for the positive electrode active materials produced in Examples 1 and 2 and Comparative Examples 1 and 2. The results are shown in Table 1 below. In Table 1, the unit of each value is nm.
[0142] [Table 1]
[0143] Evaluation example 2: Specific surface area evaluation The specific surface area was measured for the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 and 2, and the results are shown in Table 2 below. The specific surface area was measured using physical adsorption and chemical adsorption phenomena and the Brunauer-Emmett-Teller (BET) method. That is, the weight of the produced active material was measured, nitrogen was adsorbed on the surface of the active material, the amount of adsorbed nitrogen gas was measured, and the specific surface area was calculated using the BET formula.
[0144] [Table 2]
[0145] Referring to Table 2, it can be seen that in Examples 1 and 2, the specific surface area of the entire positive electrode active material including the first and second positive electrode active materials was increased compared to the comparative example.
[0146] Evaluation example 3: Evaluation of surface cobalt content In the positive electrode active materials produced in Example 1 and Comparative Example 1, a scanning electron microscope-energy dispersive spectroscopy (SEM-EDS) was performed on the surface of the single particle second positive electrode active material to measure the cobalt content ratio (at%) to the nickel and cobalt contents on the surface. FIG. 7 is a scanning electron microscope image of the second positive electrode active material of Example 1, in which the cobalt content was measured at positions 1 to 4, and the results are shown in Table 3 below. FIG. 8 is a scanning electron microscope image of the second positive electrode active material of Comparative Example 1, in which the cobalt content was measured at positions 5 to 8, and the results are shown in Table 4 below.
[0147] [Table 3]
[0148] [Table 4]
[0149] 7 and Table 3, in Example 1, there is a surface with a low cobalt content in the second positive electrode active material where the cobalt content is at a level of 19.4 at% and there is a surface with a high cobalt content where the cobalt content is at a level of 40 to 60 at%.
[0150] 8 and Table 4, in Comparative Example 1 in which the first and second positive active materials were individually cobalt-coated, the surface cobalt content of the second positive active material was in the range of about 8 to 16 at%, and there was almost no difference between the crystal planes. Also, it was confirmed that the surface cobalt coating content was in a lower range than in Example 1.
[0151] Evaluation example 4: Charge / discharge efficiency and life characteristics Each of the coin half cells of Examples 1 and 2 and Comparative Examples 1 and 2 was charged under constant current (0.2C) and constant voltage (4.25V, 0.05C cut-off) conditions to measure the charge capacity, then rested for 10 minutes, and discharged to 3.0V under constant current (0.2C) conditions to measure the discharge capacity. The ratio of the discharge capacity to the charge capacity is expressed as efficiency. The results are shown in Table 5 below.
[0152] In addition, after the initial charge and discharge, the battery was charged and discharged 50 times at 45°C and 1C, and the discharge capacity at the 50th charge was measured. The ratio (%) of the discharge capacity at the 50th charge to the initial discharge capacity is shown in Table 5 as the capacity retention rate, i.e., the life characteristics.
[0153] [Table 5]
[0154] Referring to Table 5, it can be seen that in Examples 1 and 2, the discharge capacity is increased, the charge / discharge efficiency is improved, and the high-temperature life characteristics are also improved, compared to Comparative Examples 1 and 2 in which the first and second positive active materials were individually coated with cobalt and sintered.
[0155] The first and second positive electrode active materials are all coated with cobalt, and the second positive electrode active material, which is a single particle, is only partially coated with cobalt, resulting in uneven surfaces and an increase in specific surface area. It has been confirmed that batteries using this positive electrode active material have improved characteristics such as initial discharge capacity, charge / discharge efficiency, and lifespan.
[0156] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the following claims also fall within the scope of the present invention. [Explanation of symbols]
[0157] 100: Lithium secondary battery 112: Negative electrode 113: Separation membrane 114: Positive electrode 120: Battery container 140: Sealing member
Claims
1. A first positive electrode active material including a lithium nickel-based composite oxide, the first positive electrode active material including secondary particles formed by agglomerating a plurality of primary particles, and a cobalt coating portion located on a surface of the secondary particles; A second positive electrode active material includes a lithium nickel-based composite oxide, the second positive electrode active material including a single particle and a cobalt coating portion located on a surface of the single particle, the second positive electrode active material has an uneven surface having unevenness caused by the cobalt coating and a flat surface having no unevenness; The uneven surface has a maximum roughness (R max ;peak to peak height) is 18 nm or more, and average roughness (R a ;average roughness) is 1.9 nm or more; The flat surface has a maximum roughness (R max ) is 15 nm or less, and average roughness (R a ) is 1.8 nm or less.
2. The uneven surface of the second positive electrode active material has a maximum roughness (R max 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle diameter is 20 nm or more.
3. The uneven surface of the second positive electrode active material has a root mean square roughness (R q 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the mean square roughness (roughness) is 2.3 nm or more.
4. The flat surface of the second positive electrode active material has a maximum roughness (R max 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle diameter is 14 nm or less.
5. The flat surface of the second positive electrode active material has a root mean square roughness (R q 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle diameter is 2.2 nm or less.
6. The BET specific surface area of the positive electrode active material for a lithium secondary battery including the first positive electrode active material and the second positive electrode active material is 0.2 m 2 / g to 0.6 m 2 The positive electrode active material for a lithium secondary battery according to claim 1, wherein the Mo content is 1 / g.
7. The average particle size of the first positive electrode active material is 7 μm to 25 μm, 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size of the second positive electrode active material is 1 μm to 10 μm.
8. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the first positive electrode active material is contained in an amount of 50% by weight to 90% by weight, and the second positive electrode active material is contained in an amount of 10% by weight to 50% by weight, based on the total amount of the first positive electrode active material and the second positive electrode active material.
9. The first positive electrode active material includes a lithium nickel-based composite oxide represented by the following chemical formula 1: The positive electrode active material for a lithium secondary battery according to claim 1, wherein the second positive electrode active material comprises a lithium nickel-based composite oxide represented by the following chemical formula 11: [Chemical formula 1] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O 2 In the formula 1, 0.9≦a1≦1.8, 0.3≦x1≦1, and 0≦y1≦0.7; M 1 and M. 2 are each independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or a combination thereof; [Chemical formula 11] Li a11 Ni x11 M 11 y11 M 12 1-x11-y11 O 2 In the formula 11, 0.9≦a11≦1.8, 0.3≦x11≦1, and 0≦y11≦0.7; M 11 and M. 12 are each independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or a combination thereof.
10. A first nickel-based hydroxide and a lithium raw material are mixed and subjected to a first heat treatment to prepare a first nickel-based oxide in the form of secondary particles in which a plurality of primary particles are aggregated; Mixing the second nickel-based hydroxide and the lithium raw material and subjecting them to a second heat treatment to prepare a second nickel-based oxide in the form of a single particle; The method for producing a positive electrode active material for a lithium secondary battery according to any one of claims 1 to 9, comprising mixing the first nickel-based oxide, the second nickel-based oxide, and a cobalt raw material, and subjecting the mixture to a third heat treatment.
11. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the first nickel hydroxide and the second nickel hydroxide are each independently represented by the following chemical formula 21: [Chemical formula 21] Ni x21 M 21 y21 M 22 1-x21-y21 (OH) 2 In the formula 21, 0.3≦x21≦1, 0≦y21≦0.7, M 21 and M. 22 are each independently Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr, or a combination thereof.
12. Mixing the first nickel-based hydroxide with the lithium raw material means mixing so that the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the first nickel-based hydroxide is 0.9 or more and 1.2 or less; 11. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the second nickel-based hydroxide and the lithium raw material are mixed so that a ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the second nickel-based hydroxide is 0.9 or more and 1.2 or less.
13. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the first heat treatment is carried out at a temperature in the range of 600° C. to 900° C. for 5 hours to 20 hours.
14. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the second heat treatment is carried out at a temperature in the range of 800° C. to 1100° C. for 5 hours to 20 hours.
15. 11. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein preparing the second nickel-based oxide comprises mixing the second nickel-based hydroxide and a lithium raw material, subjecting the mixture to a second heat treatment, and pulverizing the resulting product to obtain a single particle of the second nickel-based oxide.
16. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the first nickel-based oxide and the second nickel-based oxide are mixed so that a weight ratio of the first nickel-based oxide to the second nickel-based oxide is 9:1 to 5:
5.
17. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the first nickel-based oxide, the second nickel-based oxide, and the cobalt raw material are mixed such that, when a total content of metals excluding lithium in the first nickel-based oxide and the second nickel-based oxide is 100 parts by mole, cobalt contained in the cobalt raw material is 0.01 to 7 parts by mole.
18. The method for producing a positive electrode active material for a lithium secondary battery according to claim 10, wherein the third heat treatment is carried out at a temperature in the range of 650° C. to 900° C. for 5 hours to 30 hours.
19. A lithium secondary battery comprising a positive electrode containing the positive electrode active material for lithium secondary batteries according to any one of claims 1 to 9, a negative electrode, and an electrolyte.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, method of manufacturing the same, and lithium secondary battery including the same
JP2020072092A
Positive electrode active material for lithium secondary battery and lithium secondary battery including the same
JP2020077611A
Lithium metal composite oxide powder, positive electrode active material for lithium secondary battery, positive electrode, and lithium secondary battery
JP2020087879A
Lithium metal complex oxide, positive electrode active material for lithium secondary batteries, positive electrode for lithium secondary batteries, and lithium secondary battery
JP2021095298A
Cathode materials for rechargeable lithium-ion batteries
JP2021508410A